Visual evoked responses in chronic alcoholics. Issue 8 (August 1986) - Chan, Y W; McLeod, J G; Tuck, R R; Walsh, J C; Feary, P A
Abstract : Visual evoked responses (VERs) were recorded on 52 chronic alcoholics patients without Wernicke-Korsakoff syndrome, 22 of whom had cerebellar ataxia, and eight chronic alcoholics with Wernicke-Korsakoff syndrome. Abnormal VERs were found in 23% of patients without and 37% of patients with Wernicke-Korsakoff syndrome. The main VER abnormalities of all the alcoholic groups were prolonged latency and reduced amplitude of the P100 component. Improvement followed a six month period of abstinence. VERs may be useful in the early detection of alcohol induced brain damage, and in following the progress of patients with the condition.